The Annals of the Parish: 2015–2016. From Referendum to Referendum to … Referendum?. Issue 1 (February 2017) - Bort, Eberhard
Abstract : The two years since the Scottish independence referendum have been a roller-coaster ride, with the SNP picking up close to a hundred thousand new members and triumphing in the 2015 General Election, taking all but three seats in Scotland; with David Cameron winning, against the collective wisdom of the pollsters, a Westminster majority, obliging him to call his promised EU referendum; with the SNP achieving an unprecedented third Holyrood term, but losing their absolute majority; with the Scottish Tories leapfrogging Scottish Labour into second place, usurping the role of 'official opposition' at Holyrood; with Jeremy Corbyn elected UK Labour leader – not once, but twice; and, to cap it all, the vote for Brexit on 23 June, its chaotic aftermath, and the reappearance of indyref2 at the top of the agenda.